Characteristics of Effective Disaster Responders and Leaders: A Survey of Disaster Medical Practitioners. (18th May 2016) - King, Richard V.; Larkin, Gregory Luke; Fowler, Raymond L.; Downs, Dana L.; North, Carol S.
Abstract: Objective: To identify key attributes of effective disaster/mass casualty first responders and leaders, thereby informing the ongoing development of a capable disaster health workforce. Methods: We surveyed emergency response practitioners attending a conference session, the EMS State of the Science: A Gathering of Eagles. We used open-ended questions to ask participants to describe key characteristics of successful disaster/mass casualty first responders and leaders. Results: Of the 140 session attendees, 132 (94%) participated in the survey. All responses were categorized by using a previously developed framework. The most frequently mentioned characteristics were related to incident command/disaster knowledge, teamwork/interpersonal skills, performing one's role, and cognitive abilities . Other identified characteristics were related to communication skills, adaptability/flexibility, problem solving/decision-making, staying calm and cool under stress, personal character, and overall knowledge . Conclusions: The survey findings support our prior focus group conclusion that important characteristics of disaster responders and leaders are not limited to the knowledge and skills typically included in disaster training. Further research should examine the extent to which these characteristics are consistently associated with actual effective performance of disaster response personnel and determine how best to incorporate these attributes into competency models, processes, and tools for the development of an effective disaster response workforce. ( Disaster Med Public Health Preparedness . 2016;page 1 of 4)